The German Offshore-Metmasts Amrumbank West and Arkonabecken Südost - Bendfeld, Jörg (7th World Wind Energy Conference, WWEC 2008 Kingston, Ontario, Kanada, Juni 2008)

O&M for offshore windfarms based on ADCP and Waverider - Bendfeld, Jörg; Ditscherlein, Ralf; Splett, Michael; Voss, Jürgen (7th World Wind Energy Conference, WWEC 2008 Kingston, Ontario, Kanada, Juni 2008)

Possibilities of Reducing the Feed-In fluctuations of Offshore WindFarms - Bendfeld, Jörg; Splett, Michael; Tigges, Martin (7th World Wind Energy Conference, WWEC 2008 Kingston, Ontario, Kanada, Juni 2008)

Analysis of Fluctuations of Spacious Distributed Offshore Wind farms in Germany - Bendfeld, Jörg; Splett, Michael; Tigges, Martin (7th World Wind Energy Conference, WWEC 2008 Kingston, Ontario, Kanada, Juni 2008)

Biogas power plants and organic waste for energy regulating - Bendfeld, Jörg; Tigges, Martin; Splett, Michael; Voss, Jürgen (6th International Conference: ORBIT 2008 - Moving Organic Waste Recycling towards Resource Management and for Biobased Economy, Wageningen, The Netherlands, Oktober 2008)

Biogas fired fuel cell plants for compensation of offshore feed-in fluctuations - Bendfeld, Jörg; Splett, Michael; Tigges, Martin; Voss, Jürgen (Confederation of Danish Industries: Fuel Cells Science & Technology 2008 "Scientific Advances in Fuel Cell Systems", Copenhagen, Oktober 2008)

Reduction of input variability using the natural combination potential of spacious distributed offshore wind farms in the German Baltic Sea and the German Bay - Bendfeld, Jörg; Splett, Michael; Lüttig, Reinhold (Proceedings of the 9th German Wind Energy Conference (DEWEK 2008))

Possibilities of reducing the feed-in fluctuations of offshore wind farms by biogas plants - Bendfeld, Jörg; Tigges, Martin; Splett, Michael; Voss, Jürgen (Proceedings of the 9th German Wind Energy Conference (DEWEK 2008))

Wind energy extension potential in the Münsterland - Bendfeld, Jörg; Linders, Marc; Splett, Michael; Wernekinck, U. (Proceedings of the 9th German Wind Energy Conference (DEWEK 2008))

Two Years Operation of Offshore Metmast Arkona Becken Südost in the Baltic - Bendfeld, Jörg; Ditscherlein, Ralf; Splett, Michael; Voss, Jürgen (Proceedings of the 9th German Wind Energy Conference (DEWEK 2008))

Wave and Current Measurements for Offshore Windfarms - Bendfeld, Jörg; Ditscherlein, Ralf; Splett, Michael; Voss, Jürgen (Proceedings of the 9th German Wind Energy Conference (DEWEK 2008))

Local Strategies for Connecting Stations by Small Robotic Networks - Meyer auf der Heide, Friedhelm; Schneider, Barbara (Biologically-Inspired Collaborative Computing)

Bin Packing oder „Wie bekomme ich die Klamotten in die Kisten?“ - Gehweiler, Joachim; Meyer auf der Heide, Friedhelm (Taschenbuch der Algorithmen)

Planar Visibility Counting - Fischer, Matthias; Hilbig, Matthias; Jähn, Claudius; Meyer auf der Heide, Friedhelm; Ziegler, Martin (arXiv:0810.0052)
For a fixed virtual scene (=collection of simplices) S and given observer position p, how many elements of S are weakly visible (i.e. not fully occluded by others) from p? The present work explores the trade-off between query time and preprocessing space for these quantities in 2D: exactly, in the approximate deterministic, and in the probabilistic sense. We deduce the EXISTENCE of an O(m^2/n^2) space data structure for S that, given p and time O(log n), allows to approximate the ratio of occluded segments up to arbitrary constant absolute error; here m denotes the size of the Visibility Graph--which may be quadratic, but typically is just linear in the size n of the scene S. On the other hand, we present a data structure CONSTRUCTIBLE in O(n*log(n)+m^2*polylog(n)/k) preprocessing time and space with similar approximation properties and query time O(k*polylog n), where k<n is an arbitrary parameter. We describe an implementation of this approach and demonstrate the practical benefit of the parameter k to trade memory for query time in an empirical evaluation on three classes of benchmark scenes.

Proceedings of the twentieth annual symposium on Parallelism in algorithms and architectures - SPAA '08

Multiobjective Optimization of Control Trajectories for the Guidance of a Rail-bound Vehicle - Geisler, M.Sc. Jens; Witting, Dipl.-Math. Katrin; Trächtler, Ansgar; Dellnitz, Michael (IFAC Proceedings Volumes)

Domain Spanning Search for the Identification of Solution Patterns for the Conceptual Design of Self-Optimizing Systems - Klöpper, Benjamin; Podlogar, Herbert; Gausemeier, Jürgen; Witting, Katrin (2008 19th International Conference on Database and Expert Systems Applications)

Hybridizing evolutionary strategies with continuation methods for solving multi-objective problems - Schütze, Oliver; Coello Coello, Carlos A.; Mostaghim, Sanaz; Talbi, El-Ghazali; Dellnitz, Michael (Engineering Optimization)

Convergence of stochastic search algorithms to finite size pareto set approximations - Schütze, Oliver; Laumanns, Marco; Coello Coello, Carlos A.; Dellnitz, Michael; Talbi, El-Ghazali (Journal of Global Optimization)

A new approach for online multiobjective optimization of mechatronic systems - Witting, Katrin; Schulz, Bernd; Dellnitz, Michael; Böcker, Joachim; Fröhleke, Norbert (International Journal on Software Tools for Technology Transfer)